Impact of genetic polymorphisms on the pharmacokinetics and pharmacodynamics of lenvatinib in patients with hepatocellular carcinoma - Hironao Okubo; Hitoshi Ando; Kei Ishizuka; Jun-ichi Morishige; Kenichi Ikejima; Shuichiro Shiina; Akihito Nagahara (Elsevier, 2022)
This prospective study examined the impact of genetic polymorphisms on the pharmacokinetics and clinical efficacy and safety of lenvatinib, a substrate of ATP-binding transporters, in a cohort of 48 Japanese patients with hepatocellular carcinoma (HCC). Pharmacokinetic studies were performed at the start of lenvatinib therapy (day 1) and on day 15. The coefficients of variation in AUC0-24h of lenvatinib on days 1 and 15 were 44.0% and 52.4%, respectively. Although the ABCB1 3435C > A, 1236C > T, and 2677G>T/A polymorphisms did not influence pharmacokinetic parameters, the AUC0-24h values on days 1 and 15 of the ABCG2 C/A or A/A group were approximately 1.1-fold and 1.4-fold that in the ABCG2 C/C group (P = 0.164 and 0.024). There were no significant differences in AUC0-24h on days 1 and 15 between the responders (complete or partial response) and non-responders (stable or progressive disease). The AUC0-24h on day 15 in those developing anorexia of any grade was significantly higher than that without such development (P = 0.017). In multivariate analysis, ABCG2 421C > A C/A or A/A was significantly associated with the development of anorexia (odds ratio 9.009, P = 0.009). ABCG2 421C > A polymorphism could affect exposure to lenvatinib and the development of anorexia.